2020
DOI: 10.1002/aenm.201903840
|View full text |Cite
|
Sign up to set email alerts
|

A Review and Perspective on Cathodoluminescence Analysis of Halide Perovskites

Abstract: Halide perovskite solar cells have achieved a certified efficiency of 25.2%, surpassing CdTe and CIGS, which have long been regarded as the most-efficient thin-film photovoltaic materials. As this exciting class of materials continues to mature, researchers will require characterization techniques capable of exposing the interplay between structure, chemistry, and optoelectronic properties to inform processing strategies and increase both device efficiencies and long-term stability. Cathodoluminescence microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 101 publications
0
41
0
Order By: Relevance
“…This enhancement is attributed to the passivation of various recombination centres in the grain boundaries and/or at the surface of the perovskite layer. 126 Importantly, an additional CL peak at ~620 nm appears, which cannot be related to either the 3D perovskite phase or the PbI 2 -rich phase. We find similar peaks in PL measurements of GBP&SP films as well as for SP films when using a higher PEACl concentration of 3 mg/ml (see Fig.…”
Section: Energy and Environmental Science Accepted Manuscriptmentioning
confidence: 93%
See 1 more Smart Citation
“…This enhancement is attributed to the passivation of various recombination centres in the grain boundaries and/or at the surface of the perovskite layer. 126 Importantly, an additional CL peak at ~620 nm appears, which cannot be related to either the 3D perovskite phase or the PbI 2 -rich phase. We find similar peaks in PL measurements of GBP&SP films as well as for SP films when using a higher PEACl concentration of 3 mg/ml (see Fig.…”
Section: Energy and Environmental Science Accepted Manuscriptmentioning
confidence: 93%
“…To gain a better understanding about the phase or composition of the small and large bright grains observed in SEM at the surface of the perovskite films as well as their potential relevance in the context of this work, we carry out CL measurement. 126 For the Ref film, the grains which appear darker in SEM (highlighted by a green circle in Fig. 4) exhibit higher CL intensities (Fig.…”
Section: Energy and Environmental Science Accepted Manuscriptmentioning
confidence: 98%
“…Cathodoluminescence (CL) microscopy probes the radiative decay of charges generated by exposure to an electron beam and has been utilized in many studies on perovskite materials. 53 While the effect of tuning the grain size has not been systematically investigated using CL microscopy, conflicting results have been observed regarding the luminescence intensity of grains and grain boundaries. For example, Bischak et al observed a reduced CL intensity at grain boundaries and a large variation of grain-to-grain luminescence, with many large grains-surprisingly-appearing dark.…”
Section: Progress and Potentialmentioning
confidence: 99%
“…The acceleration voltage used in this study was 3 kV, corresponding to a penetration depth of 67 nm according to Monte Carlo simulations using Monte Carlo Casino (Figure S3, Supporting Information). [35] Thus, the interaction volume size in CL is significantly smaller than in confocal PL, [36] providing sufficient spatial resolution to differentiate between the grain boundary and interior.…”
Section: Charge-carrier Recombinationmentioning
confidence: 99%